2014
DOI: 10.1208/s12248-014-9604-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV Drug Development Through Computational Methods

Abstract: Abstract. Although highly active antiretroviral therapy (HAART) is effective in controlling the progression of AIDS, the emergence of drug-resistant strains increases the difficulty of successful treatment of patients with HIV infection. Increasing numbers of patients are facing the dilemma that comes with the running out of drug combinations for HAART. Computational methods play a key role in anti-HIV drug development. A substantial number of studies have been performed in anti-HIV drug development using vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 75 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…About 40 million peoples are suffering from HIV infection and Africa region is a serious victim with 25 HIV-1 protease is another key enzyme which is essential for the HIV life-cycle [13]. The protease cleaves the newly translated chain and generates required protein components to assemble the infectious HIV virions [13,14]. HIV virions become uninfectious without operative HIV protease [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…About 40 million peoples are suffering from HIV infection and Africa region is a serious victim with 25 HIV-1 protease is another key enzyme which is essential for the HIV life-cycle [13]. The protease cleaves the newly translated chain and generates required protein components to assemble the infectious HIV virions [13,14]. HIV virions become uninfectious without operative HIV protease [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, raltegravir (isentress), the first integrase inhibitor was approved by FDA in 2007 [ 13 ]. Presently about 30 antiretroviral drugs are prescribed for the clinical treatment of AIDS [ 14 ]. An improved knowledge of the structure and function viral proteins has led antiviral drug developers to design better antivirals to treat HIV infections [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures and biological activity profiles of the inhibitors have been the subject of these reviews . In a review articles belonging to 2014, anti‐HIV‐1 agents have been discussed from the computer‐aided design point of view but, not all of the available HIV‐1 entry‐related targets were considered in that review article . The present review provides updated information regarding the latest reported small‐molecule HIV‐1 entrance inhibitors considering all the computational studies reported in the literature regarding HIV‐1 entry inhibitors since 2014.…”
Section: Introductionmentioning
confidence: 99%